A new method for classifying galaxy SEDs from multiwavelength photometry - Wild, Vivienne; Almaini, Omar; Cirasuolo, Michele; Dunlop, Jim; McLure, Ross; Bowler, Rebecca; Ferreira, Joao; Bradshaw, Emma; Chuter, Robert; Hartley, Will (Oxford University Press, 2014)
We present a new method to classify the broad-band optical–near-infrared spectral energy distributions (SEDs) of galaxies using three shape parameters (super-colours) based on a principal component analysis of model SEDs. As well as providing a compact representation of the wide variety of SED shapes, the method allows for easy visualization of information loss and biases caused by the incomplete sampling of the rest-frame SED as a function of redshift. We apply the method to galaxies in the United Kingdom Infrared Telescope Infrared Deep Sky Survey Ultra Deep Survey with 0.9 < z < 1.2, and confirm our classifications by stacking rest-frame optical spectra for a fraction of objects in each class. As well as cleanly separating a tight red sequence from star-forming galaxies, three unusual populations are identifiable by their unique colours: very dusty star-forming galaxies with high metallicity and old mean stellar age; post-starburst galaxies which have formed _10 per cent of their mass in a recent unsustained starburst event; and metal-poor quiescent dwarf galaxies.We find that quiescent galaxies account for 45 per cent of galaxies with logM∗/M_ > 11, declining steadily to 13 per cent at logM∗/M_ = 10. The properties and mass function of the poststarburst galaxies are consistent with a scenario in which gas-rich mergers contribute to the growth of the low- and intermediate-mass range of the red sequence.